Isolation and characterization of pepsin-solubilized collagen from the integument of sea cucumber (Stichopus vastus) - Zainul Abedin, Md; A Karim, Alias; Ahmed, Faiyaz; A Latiff, Aishah; Chee-Yuen, Gan; Che Ghazali, Farid; Sarker, Md. Zaidul Islam (John Wiley & Sons, 2012)
BACKGROUND: Sea cucumber (Stichopus vastus) is considered an underutilized resource, since only its stomach and intestines are eaten raw as salad in a few countries and the remaining parts, especially the integument rich in collagen, is discarded.Hence a valuable by-product having potential nutraceutical and pharmaceutical applications is wasted. In the present investigation, pepsin-solubilized collagen (PSC) from the integument of S. vastus was isolated, purified and characterized. RESULTS: Sodium dodecyl sulfate–polyacrylamide gel electrophoretic analysis showed that the purified collagen was of type I, consisting of three α1 chains of approximately 122 kDa each. The peptide map of PSC digested by V8 protease was different from that of calf skin type I collagen. Fourier transform infrared spectroscopy revealed that the triple helical structure was well preserved in isolated collagen. The denaturation temperature of PSC was 21.23 ◦C and showed good gel-forming capability at pH 6.5 and 300 mmol L−1 NaCl. CONCLUSION: It is inferred that the collagen isolated from S. vastus integument has potential for use as an alternative to land-based mammalian collagen in food, nutraceuticals and pharmaceutical industries. c 2012 Society of Chemical Industry Keywords: integument collagen; sea cucumber; gel